Diplomatic Embassy ruling in accordance to Ibn Taymia's and comparing it to the international law - Nour, Najla bint Mohammed Burhan Mohamed (Journal of Humanities & Social Sciences, 2018)
The present research is to represent a very important topic which is the international relation in general and Embassy as per Islamic law in particularly Ibin Taymia concept has been taken here in consideration. He has been living during the period between seven and eight centuries (661- 728). Such period is a very hard one in the Islamic History as most of Islamic Countries did pass by difficult situation politically, socially, economically, scientifically, and religiously. May trends had been appeared during his age about the international relation, Embassy in Islamic law and individual Embassy as assort of political deed. Embassy had been to appear as a vital tool in the relation among countries. The matters of war, reconciliation, ceasefire, treaties among Muslims and none Muslims do in need for mutual representatives. Those people and their role have given them many concessions and protections in Islamic law. But it was known that they will be subject to Islamic law if they committed crimes and violations against either Allah or civilian’s rights. This is most Islamic sayings as well as Sheik El- Islam bin Taymia. It is to cease these deeds against diplomatic justification.The diplomatic Embassy as an International Relation will be treated under such concept as it is part of Islamic law which is based on revelation of Allah. The Embassy treatment rule is based on Islamic law. Morals and ethics that are distinguished by consistent and righteousness not like international law. It has laws set for just to serve strong nation and dominance on world.
Keywords: embassy; diplomacy; security contract; ambassadors; trustees; diplomatic immunity